IMPLEMENTASI APLIKASI “PETANI” DAN “HUKAKU” DALAM UPAYA PENINGKATAN PENGETAHUAN TENTANG PRODUKTIVITAS DAN PENDAPATAN PERTANIAN SAMOSIR SUMATERA UTARA - Henny Febriana Harumy; Hanifah ZN. Amrul (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2018)
The problem that is carried out by farmers in Samosir is that it is difficult for them to sell their crops at a higher price. Apart from that, agricultural products have never been used. Usually, the farmer will turn on the waste or the rest of the production. Also, the problem that occurs is the attack of fungi on the onion plant. Until now there are no experts who can damage the farmers. Also, the question that arises is the attack of mushrooms on the onion plant. Until now there are no experts who can hurt the farmers. Solution to overcome this problem by using the "HUKAKU" Auction Application Farmers can sell agricultural products at reasonable and competitive prices and "PETANI" Application Farmers can communicate and discuss with agricultural experts. The method used today is using learning services that provide training and software assistance for workers to increase productivity. The results of this activity are farmers, and they are those who get access to information and information about agriculture and pest control.